Study on properties of multipole switched reluctance motor designed for multichannel operation – single channel operation analysis - Korkosz, Mariusz; Bogusz, Piotr; Prokop, Jan; Zasowski, Piotr (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The following paper deals with the multipole design of the switched reluctance motor (SRM). The design is intended to facilitate the four-channel operation of the motor. Due to multipole design of the rotor and multichannel operation abilities, there are numerous potential configurations for powering the poles in each phase. Analysis of a selection of such configurations was carried out, including multichannel (MC) operating conditions (e.g., single-channel operation (SCO)). A mathematical model of three-phase MC SRM is also presented. The static electromagnetic torque characteristics were obtained together with the self-and mutual inductance characteristics. Selected laboratory test results are likewise presented in the paper.